A CLINICAL STUDY OF SIDDHA HERBAL PREPARATION – M V KASHAYAM FOR THE TREATMENT, CONTROL, AND MANAGEMENT OF COVID-19 - SP, MALARKANNAN; P, DHARUMARAJAN; MK, HARIYOHESH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: At present, the pandemic COVID-19 by novel coronavirus causing severe mortality and losses to the human and no specific medicine to cure. Siddha is an ancient system of medicine used in using a variety of medicinal herbs to cure diseases of viral and unknown origin. Method: The herbal medicine M V Kashayam prepared as per Siddha formula administered at the dose rate of 150 ml for every 6-h interval for Reverse Transcription–Polymerase Chain Reaction (RT – PCR) positive patients Results: The prepared MV Kashayam can able to provide RT-PCR negative in 87.5% of cases within 4–6 days and 97.5% negatives in 12 days. The body temperature, Oxygen saturation level (SPO2), and respiration level become normal within 3 days. Conclusion: The Siddha medicine, MV kashayam may be used as herbal medicine to treat the COVID-19 patients for earlier recovery and as a preventive measure to enhance immunity.